2010
DOI: 10.1002/mds.23023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dual‐tasking aspects in frequent and infrequent fallers with progressive supranuclear palsy

Abstract: Progressive supranuclear palsy (PSP) is a rare neurodegenerative disease with no sufficient therapeutic options to date. Falls are the most devastating feature. The causes of these falls are not well understood. To test the impact of PSP-associated motor and cognitive features on falls, 26 PSP patients were prospectively recruited and divided into frequent fallers (> one fall/month, 18 patients) and infrequent fallers ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Moreover, individuals with PSP (and particularly those who experience a high rate of falls), exhibited marked SL dysfunction during DT walking. 35 Together, these reports underscore the importance of the PPN as one of several regions contributing to FoG and attention regardless of disease pathophysiology.…”
Section: Ppn Structural Connectivity and Dt Interferencementioning
confidence: 81%
“…Moreover, individuals with PSP (and particularly those who experience a high rate of falls), exhibited marked SL dysfunction during DT walking. 35 Together, these reports underscore the importance of the PPN as one of several regions contributing to FoG and attention regardless of disease pathophysiology.…”
Section: Ppn Structural Connectivity and Dt Interferencementioning
confidence: 81%
“…In addition, Probst et al [22] reported presence of neurofibrillary fibers, neuropil threads throughout the basal ganglia and brainstem in PSP. In addition impairment of balance in PSP has been attributed to central vestibular dysfunction [9], deficits in motor programming [23], abnormal otolith-mediated reflexes [24], synergistic deterioration of brainstem and higher cortical functions [25] and involvement of cerebellum [26].…”
Section: Discussionmentioning
confidence: 99%
“…As a next step, dual-task costs (DTC) were determined, reflecting the relative performance in the dual-task setting as compared to the single task setting. They were calculated using the following formula according to Bock (2008) and Lindemann et al (2010): DTC [%] = (single task-dual task) / (single task) * 100. This formula gives information about the percentage change relative to the single-task value.…”
Section: Methodsmentioning
confidence: 99%